Long term sustained therapeutic effects of percutaneous posterior tibial nerve stimulation treatment of neurogenic overactive bladder in multiple sclerosis patients: 12‐months results. Issue 1 (9th September 2015) - Canbaz Kabay, Sibel; Kabay, Sahin; Mestan, Emine; Cetiner, Mustafa; Ayas, Selahattin; Sevim, Mehmet; Ozden, Hilmi; Karaman, Handan Ozisik
Abstract : Aims: The aim of this study is to determine the sustained therapeutic efficacy and treatment intervals for PTNS in NOAB with MS, offering periodic additional treatments during 1 year in patients who completed an initial course of 12 consecutive weekly sessions. Methods: A total of 34 patients enrolled to the PTNS treatment and 21 patients completed the 1 year PTNS treatment with a tapering protocol of 6, 9, and 12 months of therapy, respectively. After 12 weeks of therapy, PTNS was applied at 14 day intervals for 3 months, 21 day intervals for 3 months, and 28 day intervals for 3 months. The patients completed a 3‐day voiding diary at 3rd, 6th, 9th, and 12th month. The patients requested to complete validated questionnaires (ICIQ‐SF, OAB‐V8, OAB‐q SF) were carried out within 3‐month intervals thereafter during their enrolment in the study. Results: A total of 21 patients were enrolled in the study. Of these 5 (23.8%) were men and 16 (76.2%) women. The improvements for all voiding diary parameters were significant in the 6th, 9th, and 12th months when compared with baseline. Mean values between baseline and 12 month parameters suggested that daytime frequency decreased by 5.4 voids daily, urge incontinence decreased by 3.4 episodes daily, urgency episodes decreased by 7.4 episodes daily, nocturia decreased by 2.6 voids, and voided volume improved by a mean of 72.1 cc. Conclusion: These results have demonstrated NOAB symptom improvement in MS patients can be achieved with 12 weekly PTNS treatments which show excellent durability over 12 months. Neurourol. Urodynam. 36:104–110, 2017 . © 2015 Wiley Periodicals, Inc.